THE ROLE OF ADULT EDUCATION PROGRAMMES IN POVERTY ALLEVIATION STRATEGIES IN ILORIN WEST LOCAL GOVERNMENT AREA, KWARA STATE, NIGERIA - KAYODE, SADIQ TOYIN; SHOLAGBERU, A. O; YAKUBU, TOYIN IBRAHIM (Sokoto Educational Review, 2025)
This study explores the role of adult education in poverty alleviation strategies, using Ilorin West Local Government Area, Kwara State, as a case study. It posits that adult education is a crucial tool for empowering individuals with the skills and knowledge needed to improve their socioeconomic status. A descriptive research design was adopted. The study population comprised all 2,500 adult education learners in Ilorin West Local Government Area. A sample of 100 adult learners and 20 facilitators was selected. Two research questions and two hypotheses guided the study. Findings highlight a positive correlation between participation in adult education programs and improved economic outcomes, including increased employment opportunities, higher income levels, and an enhanced quality of life. Data were analyzed using percentages. The study concludes that adult education is a vital component of comprehensive poverty alleviation strategies and recommends policy interventions to support and expand these programs. The implications of this research underscore the need for sustained investment in adult education to foster sustainable development and economic growth in Kwara State and similar contexts. DOI: https://doie.org/10.0228/SER.2025187146